2011
DOI: 10.1159/000322798
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Transcranial Magnetic Stimulation in Vascular Dementia

Abstract: Vascular dementia (VaD) is a clinical syndrome that encompasses a wide spectrum of cognitive disorders caused by cerebrovascular disease. The subcortical ischemic form of VaD is clinically homogeneous and a major cause of cognitive impairment in the elderly. Vascular lesions contribute to cognitive decline in neurodegenerative dementias, and VaD and Alzheimer’s disease often coexist and share clinical features and multiple neurotransmission involvement. These similarities have led several investigators to use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 191 publications
3
27
0
Order By: Relevance
“…In the last years, a number of studies have shown abnormalities in TMS assays of cortical function in dementias, namely an increased excitability of the motor cortex in both Alzheimer's disease (AD) [77] and VaD [78]. …”
Section: Transcranial Magnetic Stimulation: Basic Principles and Amentioning
confidence: 99%
“…In the last years, a number of studies have shown abnormalities in TMS assays of cortical function in dementias, namely an increased excitability of the motor cortex in both Alzheimer's disease (AD) [77] and VaD [78]. …”
Section: Transcranial Magnetic Stimulation: Basic Principles and Amentioning
confidence: 99%
“…In the last years, several investigators have used transcranial magnetic stimulation (TMS) to define the electrophysiological profile of several neuropsychiatric disorders [11], [12], physiological brain aging [13], different models of cognitive decline [14], [15] and some systemic diseases with a neurological involvement [16], [17]. TMS is a safe and non-invasive neurophysiological technique specifically able to evaluate the excitability and functioning of the primary motor cortex and the cortico-spinal tract [18].…”
Section: Introductionmentioning
confidence: 99%
“…Vascular mechanisms are also advocated, but in non-demented vascular patients there is no change in rMT [22]. It could be more common in the later stage of AD [23] and influence the level of the motor threshold. This was not the case in our patients as they were in the early stage of the disease, and their brain MRIs showed neither atrophy in the area of the motor cortex nor vascular damage.…”
Section: Discussionmentioning
confidence: 99%